(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: The process of groundwater recharge is considered as one of the most important processes for the management of water resources, both surface and groundwater. Materials and Methods: The current study uses the application of the Analytical Hierarchical Process (AHP) model in geospatial analysis to delineate potential areas for groundwater recharge. The foundations of this model were laid by Saaty. The analytical method was used to calculate the natural weight of the factors individually, according to the size of the groundwater recharge potential. Each factor within the GIS environment was reclassified according to the AHP technique. Results: The results show that in large regions of the study area, about 38.7% have poor to very poor recharge potential, 29.3% of the area is moderate, 19.5% of the area has good recharge potential, and the remaining area (12.3%) has very good potential for groundwater recharge. The soil factor showed that it was the most influential factor in the delineation of groundwater recharge areas for the study area. Conclusion: The potential zones of very good and good groundwater occupy 312.67 and 495.70 km2, respectively, which are 12.3% and 19.5% of the study area. It appears from the map of groundwater potential zones that the areas of good and very good recharge are mostly prominent in the sedimentary plains with low slopes and high drainage density. Also, a small part of it appears in the mountainous areas, which represent the main recharge areas for the falling rainwater.